Leaves epidermal characters of forbs from the western chaco, San Luis (Semiárida, 2020)
The leaf epidermis of the following forbs from the Westem Chaco region (San Luis Province, Argentina) are analized and lIIustrated: Conyza bonariensis, Schkuria pinnata, Xanthium spinosum, Cryptantha mendocina, Evolvulus seticeus, Cucurbitella asperata, Ibicella parodii, Clematis denticulata, Solanum juvenale y Tribulus terrestris. The characteres used for taxonomíc determination are those useful for the identification of small fragments such as: cell walls, trichomas, stomata and cuticular omamentatlon. A key for the identification of these species is presented.
Keywords: leaf epidermal; forbs; Western Chaco